Study protocol for an international registry observational study evaluating clinical outcomes of transcatheter versus standard surgical mitral valve operation for secondary mitral regurgitation: the TEERMISO study - Antonio Salsano; Francesco Nappi; Sanjeet Singh Avtaar Singh; Cristiano Spadaccio; Yasushige Shingu; Satoru Wakasa; Antonio Fiore (BMJ Open)
Background Secondary mitral regurgitation (SMR) is a condition affecting the left ventricle (LV) rather than the mitral valve (MV). If the MV remains structurally unchanged, enlargement of the LV or impairment of the papillary muscles can occur. Several mechanical interventions are available to dictate the resolution of MR. However, there is a lack of robust data to compare MV replacement, MV repair (including subvalvular repair) and transcatheter mitral valve procedures (TMVp). This study aims to compare the effectiveness and clinical outcomes of TMVp using the edge-to-edge mitral valve repair technique and standard surgical mitral valve procedures in patients with SMR.Methods and analysis Five cardiac surgery centres from four European countries and Japan have collaborated to create a multicentre observational registry (TEERMISO). The registry will enrol consecutive patients who underwent mechanical intervention for SMR between January 2007 and December 2023. The investigators assessed the difference between replacement and repair for both the standard surgical approach and the transcatheter procedure. The main clinical outcome will be the degree of LV remodelling as assessed by the Left Ventricular End-Diastolic Volume Index at 10 years. The study will measure several secondary endpoints, including all-cause mortality as the primary endpoint, followed by functional status, hospitalisation, neurocognition, physiological measures (echocardiographic assessment), adverse events and reoperation.Ethics and dissemination Ethics approval was obtained in Montpellier University Hospital on 24 May 2022 (Institutional Review Board Approval Number: IRB-MTP_2022_05_202201143). The results of the main study and each sub-analysis will be submitted for publication in a peer-reviewed journal.Trial registration number NCT05090540.